(untitled) (Acta Scientiarum. Biological Sciences, 2022)
Hesperozygis ringens (Lamiaceae), popularly known as espanta-pulga, is a threatened species endemic to rocky and sandy regions of the Pampa biome. One factor that can influence the low number of individuals of a species is a low seed germination rate influenced by temperature and/or light. Thus, the objective of this study was to evaluate the influence of light and temperature on the seed germination of H. ringens. The seeds of two lots were sown on a paper substrate and maintained in BOD chambers at temperatures of 15, 20, 25 and 30ºC in the presence and absence of light. The germination speed rate was evaluated every 3 days for 21 days. The experiment was completely randomized with treatments that had a 4 x 2 factorial design. The first visible sign (protrusion of the primary root) of germination was observed seven days after sowing. Germination occurred both in the presence and absence of light and the lowest temperatures significantly influenced the germination process and germination speed. For germinating the species, 15°C was the most favorable temperature compared to 20, 25 and 30°C. It can be concluded that a temperature of 15ºC favors the germination process of H. ringens seeds, which are insensitive to light.